Harvard business review on green business strategy (Harvard Business School Pub., 2007)
Just a decade ago, the term "green building strategy" evoked visions of fringe environmentalism and a high cost for minimal good. More recently, there's been a large shift in perception, an awakening of social consciousness, and a realization that a strategy good for the world can also be good for your bottom line. Green Business Strategy is no longer an option; the future depends on it. This collection of HBR articles gets to the heart of why you should and must put a socially-responsible strategy at the top of your CEO's agenda